Dyeing of Biotreated and Gamma Irradiated Cotton Fabric using Direct Yellow 12 and Direct Yellow 27. Issue 4 (3rd July 2016) - Usman, M.; Adeel, S.; Haider, W.; Ghaffar, A.; Rehman, F.; Ali, M.
ABSTRACT: The present study is concerned with dyeing of gamma irradiated and biotreated cotton fabric using direct dyes. Dyeing was performed after exposing fabric to gamma rays at 18 and 14 kGy for Direct Yellow 12 and Direct Yellow 27, respectively, using Cs-137 irradiator. It was found that dyeing of biopolished cotton after gamma rays treatment gives good color strength at 50 °C for 70 min keeping M:L of 1:40 in the presence of 4 g/L of salt using Direct Yellow 12. While for Direct Yellow 27, better results were obtained at 50 °C for 50 min keeping M:L of 1:40 in the presence of 2 g/L salt. The biotreatment of fabric before gamma rays irradiation has reduced dyeing time and amount of salt used which shows that it is the time effective tool for direct dyeing of cotton. The improvement in colorfastness properties show that biotreatment before gamma ray treatment is an effective method for modifying textile processing.